Arrhythmias in children undergoing orthotopic heart transplantation - Doğan, Eser; Ergin, Fırat; Beyter, Mehmet B.; Kaşıkçı, Gülçin K.; Ön, Şeyma Ş.; Ay, Oğuzhan; Levent, Reşit E.; Engin, Çağatay; Ülger, Zülal (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Heart transplantation (HT) is the only treatment option in children with heart failure secondary to cardiomyopathies and non-reparable congenital heart diseases. Methods: We performed a retrospective clinical data review of all consecutive pediatric patients (aged 2- 18 years) who underwent orthotopic HT for advanced heart failure at our institution between January 2007 and January 2023. Clinical, procedural, and follow-up data were collected and comprehensively analyzed. Results: We identified 27 children (66.7% males) with a median age of 15 years (IQR, 7-16) and a median weight of 45 kg (IQR, 22-66) at the time of the intervention. 24 patients (88.8%) were diagnosed with dilated cardiomyopathy, 2 (7.4%) with restrictive cardiomyopathy, and 1 (3.7%) with hypertrophic cardiomyopathy. On a median follow-up of 35.07 months (IQR, 13.13-111.87), arrhythmias were detected in 9 (33%) patients. Three patients developed symptomatic sinus node dysfunction at 18, 25, and 38 days and received permanent pacemakers. One patient developed a complete AV block during acute rejection at 76 months and received a temporary pacemaker. Two patients developed chronic sinus tachycardia at 4 and 16 months and were treated with Beta-blockers after eliminating all causes of sinus tachycardia. One patient developed a complete right bundle branch block at 12 months. One patient developed ventricular extrasystole at 10 months and was found to have grade 2 rejection. An Atrial extrasystole was detected in one patient at 96 months. We did not identify significant risk factors for arrhythmias post-HT. Discussion: After pediatric HT, early-onset rhythm disturbances, often attributed to surgery-related issues such as sinus node dysfunction, may necessitate invasive treatments like permanent pacemaker therapy. Close monitoring post-transplantation is crucial, and routine follow-up with Holter ECG is necessary to identify potential rhythm disorders even in the absence of symptoms. Rhythm disturbances that develop during follow-up can serve as early indicators of graft rejection and should be carefully evaluated.